Estimation of injury simulation in international men's soccer - Rosenbaum, D. A.; Saunders, W.; Nelson, C. M.; Rosenbaum, B. R. (International Journal of Sports Medicine, 2010)
The aim of this study was to determine the frequency of apparent injury incidents in men's international soccer and attempt to estimate what proportion of these incidents are authentic. Broadcast recordings of 89 group stage games from 4 tournaments were reviewed to identify incidents in which a player behaved as if injured. Apparent injuries were considered definite if a player withdrew from participation within 5 min or if bleeding was visible. The remaining incidents were considered questionable. A total of 980 apparent injuries were observed at a rate of 5.63/team game. The definite injury rate was only 0.41/team game vs. 5.22/team game for questionable injuries. Definite injuries were associated with on-field treatment (P<0.001) and stretcher (P<0.001) while questionable injuries were associated with fouls (P0.001), yellow cards (P=0.013), and the first half (P=0.001). Questionable injuries were more associated with the final 1/3 of the second half than the initial 2/3 (P=0.039). For the 24 games of the 2007 AFC Asian Cup there was an association between questionable injuries and a contact mechanism (P<0.001). The range of the rate of questionable injury was 4.17-5.4 by confederation. This information may assist soccer governing bodies in developing plans to prevent injury simulation behavior.